MESIODISTAL WIDTH AND HEIGHT OF PRIMARY ANTERIORS OF MAXILLA AMONG INDIAN POPULATION - Krisna Malay, Kausalyah; Sudhan, Madhu; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
AIM: The aim of this research is to evaluate the mean value of mesiodistal width and height of maxillary primary anterior crowns of children in order to document and provide a record of maxillary anterior deciduous crown sizes.OBJECTIVE: Evaluation of the mean value size of maxillary primary anterior crown of children is to document and provide a record of maxillary anterior deciduous crown sizes to ease the selection of crown size during clinical procedure for children who requires such treatments. Materials and Methods: The study was conducted on a sample size of 100 pedodontic patients visiting Saveetha Dental College aged less than 7 years old. The height and width of maxillary anterior primary teeth was taken intraorally using k-files and measured with endo block. And mean value was calculated from the recorded measurement of maxillary central incisors, maxillary lateral incisors, and maxillary canines. RESULTS: The maxillary incisors showed less variability in size than the maxillary canines. The greatest variability was seen in the mean height and width of the maxillary lateral incisors and maxillary canines. The maxillary lateral incisors showed the least variability of all the maxillary anterior teeth.CONCLUSION: This study highlighted mean value height and mesiodistal width of maxillary central incisors, maxillary lateral incisor, and maxillary canines in primary dentitions. This value is documented in order to ease the crown size selection during particular treatment procedure.